Effect of Tetraethyl Thiuram Disulphide (Disulfiram) on Metabolism of Trichloroethylene in Man. Issue 3 (July 1962) - Bartoníček, V.; Teisinger, J.
Abstract : The amounts of trichloroethanol and trichloroacetic acid excreted in the urine of four subjects who inhaled trichloroethylene in a concentration of about 1 mg./l. for a period of five hours in a laboratory experiment were determined. This experiment was repeated under the same conditions after tetraethyl thiuram disulphide (disulfiram) had been given in divided doses, totalling 3 or 3·5 g. The elimination of trichloroethanol in urine was decreased by 40 to 64%, and of trichloroacetic acid by 72 to 87%. The trichloroethylene excreted by the lungs in two of the subjects increased up to 65% of that retained within five hours. It is concluded that tetraethyl thiuram disulphide (disulfiram) strikingly inhibits the oxidation of trichloroethylene. The possible therapeutic use of this substance in cases of severe peroral trichloroethylene intoxication is discussed.